2014
DOI: 10.1097/mph.0b013e318290d503
|View full text |Cite
|
Sign up to set email alerts
|

Bacteremia Due to Imipenem-resistant Roseomonas mucosa in a Child With Acute Lymphoblastic Leukemia

Abstract: Roseomonas are described as opportunistic pathogens rarely involved in human infections. Their identification requires molecular methods and their antimicrobial susceptibility pattern varies according to the species. We report the first case of bacteremia due to Roseomonas mucosa in a child with leukemia and reviewed pediatric cases of Roseomonas infection, for which undoubted strain identification was available. Favorable outcome was observed despite resistance to numerous β-lactams that may account for delay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 12 publications
(25 reference statements)
1
12
0
Order By: Relevance
“…In general, R.mucoca was resistant to β-lactam antibiotics, such as piperacillin-tazobactam, ampicillin, extended spectrum cephalosporins (cefrazidime, cefepime) and colistin, while it was full susceptibility to aminoglycosides (amikacin, gentamicin) and fluoroquinolones (levofloxacin, ciprofloxacin), and usually susceptible to carbapenems (imipenem, meropenem) [ 2 , 7 9 ]. Consistent to our results, the previous case series reported that 100% of R.mucoca isolated was resistant to piperacillin-tazobactam [ 17 ]. According to the study of a contemporary multicenter cohort in Italy, approximately 73% of non-HEACK Gram-negative bacilli IE patients were treated with penicillin or cephalosporin (penicillin–penicillinase inhibitor or a third-generation cephalosporin), variably combined with carbapenem and aminoglycoside or fluoroquinolone [ 15 ].…”
Section: Discussionsupporting
confidence: 93%
“…In general, R.mucoca was resistant to β-lactam antibiotics, such as piperacillin-tazobactam, ampicillin, extended spectrum cephalosporins (cefrazidime, cefepime) and colistin, while it was full susceptibility to aminoglycosides (amikacin, gentamicin) and fluoroquinolones (levofloxacin, ciprofloxacin), and usually susceptible to carbapenems (imipenem, meropenem) [ 2 , 7 9 ]. Consistent to our results, the previous case series reported that 100% of R.mucoca isolated was resistant to piperacillin-tazobactam [ 17 ]. According to the study of a contemporary multicenter cohort in Italy, approximately 73% of non-HEACK Gram-negative bacilli IE patients were treated with penicillin or cephalosporin (penicillin–penicillinase inhibitor or a third-generation cephalosporin), variably combined with carbapenem and aminoglycoside or fluoroquinolone [ 15 ].…”
Section: Discussionsupporting
confidence: 93%
“…2e4 Paediatric studies are limited, but the literature suggests that the same risk factors may be encountered. 34,35 All of the patients in our report had a long-term intravascular catheter and acquired their infection nosocomially. They were also all receiving immunosuppressive drugs (from corticosteroids to myeloablative bone marrow transplant conditioning) and had received a broad-spectrum antibiotic within the previous two weeks.…”
Section: Discussionmentioning
confidence: 95%
“…8,9,15 None of the ablated catheters was positive for achromobacter, but, as previously reported for other NFGNB, the culture duration (72 h) was probably too short for these slowgrowing strains, as reflected by the usually long time to blood culture positivity. 35 According to the criteria applied, it is difficult to affirm that these cases of bacteraemia were catheter-related because no peripheral blood cultures were performed, bacteraemia was definitely catheter-related for four patients because sepsis was refractory to intravenous antibiotics but resolved after catheter removal, or all patients had catheter-related infections because qualitative positive blood cultures obtained from a CVC are sufficient for the diagnosis in paediatric oncology patients. 22,24,36 The results of studies concerning catheter removal for patients with catheter-related bacteraemia due to NFGNB are controversial.…”
Section: Discussionmentioning
confidence: 98%
“…Because of their low pathogenicity, Roseomonas species rarely cause infections in humans; thus, its clinical features are not yet fully understood. To elucidate the clinical characteristics of Roseomonas bacteremia in children, we reviewed previous literature ( Table 2 ) [ 8 , 9 , [14] , [15] , [16] , [17] , [18] ]. A search of MEDLINE from its inception in 1996 revealed only 12 such cases.…”
Section: Discussionmentioning
confidence: 99%
“…However, commercial microbiologic kits using a phenotypic approach may result in misidentification, and accurate bacterial identification of the organisms at the species level requires genetic techniques. As in previous cases [ 14 , 17 , 20 ], we identified the R. mucosa strain using 16S rDNA sequencing.…”
Section: Discussionmentioning
confidence: 99%